Energy management system using RF module - Vardhan R. Harsha; Reddy C. Harinatha; Prasad R. Ramanjan; Pakkiraiah B.; Vardhan L. Harsha (E3S Web of Conferences)
The demand for electrical energy is steadily increasing, and the buildings sector represents one of the largest energy end use. The larger amounts of that energy are wasted due to unnecessary heating and cooling. Several studies have shown that the major reason for this behaviour lies in poor controls and the lack of feedback information. In this paper we develop a device that controls home appliances from distance with integrated acknowledgement feature. Unlike the conventional system present in houses, where one has to manually switch on and off the appliances. The proposed system allows the owner of the house to control the appliances wirelessly through a centred location. This is extremely convenient for users as they can control their house loads at any time and from any place (depends on range of the RF module). This system consists of an Arduino microcontroller with various sensors such as a temperature sensor, simple RF modules as well as actuators to control the air conditions. The simple measures show that using the suggested system can save the electricity cost for every test case.